Trabalho docente: representações discursivas de duas professoras de língua inglesa - Araújo, Adriana de Oliveira Gomes (2010)
This research is based in the field of Applied Linguistics, with the theoretical assumptions of Interactionismo Sociodiscursivo - ISD (BRONCKART, (2003 [1999], 2008). For this theory, language is essential to human development, and it still permits us to analyze the act of speaking, which is consolidated through oral and written texts. Being this research based on a qualitative and interpretative review, the analyses of these texts occurs in an ample way, once it also considers other studies such as Ergonomics and Clinical Activity in proposing its analytical categories. We were interested in investigating the discursive representations of two English teachers from Tocantins State about their work, since we believed that this search would expand our conception in relation to teaching, providing a better understanding of the teacher in relation to his/her act. We Chose these teachers because they are experiencing a new reality of work outside the classroom as curriculum advisors. Our specific aim is to ensure that the research participants evaluate their own work from this new practice, comparing the representations of these teachers that are now included in this new context, and identifying which linguistic choices show their interpretations of the teaching act. We believe that this new reality of work would influence the discursive representations of the teachers regarding their professional performance. The research central question is: in what way these teachers evaluate their practice through the exercise of the new function. The corpus was collected from a semistructured interview and reflective narratives exchanged between the teachers and this researcher. The analysis of data showed that when they enunciate, the research participants allowed that voices and many enunciative positions emerged in their speeches. Thus, the teachers evaluate their actions, not only as teachers in particular and collective contexts of work, but as curriculum advisors.